A Translation Analysis of Adverbial Phrases in Angels and Demons Novel and by Ingrid Dwijani Nimpoeno - Dwi Puspitasari, Linda (2016)
The Objectives of the research are to identify the translation shifts of adverbial phrases in the Angels and Demons Novel by Ingrid Dwijani Nimpoeno, and to explain the translation accuracy of Angels and Demons Novel. This research belongs to descriptive qualitative research. The objects of the study are Adverbial phrase found in Angels and Demons Novel by Ingrid Dwijani Nimpoeno. The data of this research are clauses and sentences containing adverbial phrases found in Angels and Demons Novel by Ingrid Dwijani Nimpoeno. The writer uses the methods documentation to collect the data. The result of this research shows that are 25 translation shift of adverbial phrases found in Angels and Demons Novel. From 106 data of adverbial phrase, there are AdvP1 translated into VP consists of 11 data or 10,4%, AdvP1 translated into NP consists of 31 data or 29,2%, AdvP1 translated into Adv consists of 10 data or 9,4%, AdvP1 translated into Adj consists of 4 data or 3,8%, AdvP1 translated into N consists of 13 data or 12,3%, AdvP1 translated into V consists of 2 data or 1,9%, AdvP1 translated into Sentence consists of 2 data or 1,9%, AdvP2 translated into Adv consists of 3 data or 2,8%, AdvP4 translated into VP consists of 2 data or 1,9%, AdvP4 translated into Adj consists of 2 data or 1,9%, AdvP5 translated into N consists of 1 data or 0,9%, AdvP6 translated into Adj consists of 2 data or 1,9, AdvP7 translated into VP consists of 1 data or 0,9%, AdvP7 translated into V consists of 1 data or 0,9%, AdvP7 translated into Sentence consists of 1 data or 0,9%, AdvP9 translated into NP consists of 3 data or 2,8%, AdvP9 translated into Adv consists of 5 data or 4,7%, AdvP10 translated into AdvPe consists of 10 data or 9,4%, and deletion consists of 2 data or 1,9%. In accuracy there are 3 grades. The grades are accurate, less accurate, and not accurate. From the table above, the researcher gets the percentage of translation accuracy. First, there are 1493 data or 91,5% of accurate translation, 111 data or 6,8% data of lees accurate, and 27 data or 1,7% data of not accurate. Based on the percentage of category of translation quality above, the majority of translation quality is high accurate level.